Early-Onset Neonatal Sepsis. Issue 30 (July 2015) - Chiesa, Claudio; Pacifico, Lucia; Osborn, John F.; Bonci, Enea; Hofer, Nora; Resch, Bernhard; Marsha, Medows.
<x xml:space="preserve">Abstract</x> Abstract To perform a systematic review assessing accuracy and completeness of diagnostic studies of procalcitonin (PCT) for early-onset neonatal sepsis (EONS) using the Standards for Reporting of Diagnostic Accuracy (STARD) initiative. EONS, diagnosed during the first 3 days of life, remains a common and serious problem. Increased PCT is a potentially useful diagnostic marker of EONS, but reports in the literature are contradictory. There are several possible explanations for the divergent results including the quality of studies reporting the clinical usefulness of PCT in ruling in or ruling out EONS. We systematically reviewed PubMed, Scopus, and the Cochrane Library databases up to October 1, 2014. Studies were eligible for inclusion in our review if they provided measures of PCT accuracy for diagnosing EONS. A data extraction form based on the STARD checklist and adapted for neonates with EONS was used to appraise the quality of the reporting of included studies. We found 18 articles (1998–2014) fulfilling our eligibility criteria which were included in the final analysis. Overall, the results of our analysis showed that the quality of studies reporting diagnostic accuracy of PCT for EONS was suboptimal leaving ample room for improvement. Information on key elements of design, analysis, and interpretation of test accuracy were frequently missing. Authors should be aware of the STARD criteria before starting a study in this field. We welcome stricter adherence to this guideline. Well-reported studies with appropriate designs will provide more reliable information to guide decisions on the use and interpretations of PCT test results in the management of neonates with EONS.